1971
DOI: 10.1084/jem.134.5.1335
|View full text |Cite
|
Sign up to set email alerts
|

H-2-LINKED GENETIC CONTROL OF IMMUNE RESPONSIVENESS TO OVALBUMIN AND OVOMUCOID

Abstract: Immune responsiveness of inbred mice to low doses of ovalbumin or ovomucoid is under control of single dominant genes closely linked to alleles of the H-2 locus. High responsiveness to ovomucoid is linked with the H-2a and H-2k alleles, and to ovalbumin with the H-2b, H-2d, and H-2q alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…It has been demonstrated that induction of a specific IgE antibody is invariably accompanied by induction of an antigen-specific IgG (Vaz et al, 1970(Vaz et al, , 1971Yamanishi et al, 2003). This is especially the case for sub-classes of IgG that are regulated in a manner similar to IgE (as surrogates for IgE).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that induction of a specific IgE antibody is invariably accompanied by induction of an antigen-specific IgG (Vaz et al, 1970(Vaz et al, , 1971Yamanishi et al, 2003). This is especially the case for sub-classes of IgG that are regulated in a manner similar to IgE (as surrogates for IgE).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Merryman (personal communication) has shown that the ability of mice to respond to the linear synthetic polypeptide GAT10 is also a property of the K region of the H-2 complex. Vaz et al (26) have also shown that the ability to respond to low doses of ovomucoid and bovine 3'-globulin is a property of the K region of the H-2 complex. In each of these cases, localization was accomplished through the use of H-2 recombinants produced by Stimpfling from crossovers between H-2 '~ and H-2 b.…”
Section: Discussionmentioning
confidence: 99%
“…For more complex immunogens, genetic regulation of responsiveness in this species has been reported for limiting immunogenic doses of certain proteins (9,10). This dose-dependent expression of Ir genes was attributed to immunological stimulation by those determinants which were both most immunopotent and under the control of a specific If gene (25).…”
Section: Discussionmentioning
confidence: 99%